T cells in peripheral blood after gluten challenge in coeliac disease. Issue 9 (11th August 2005) - Anderson, R P; van Heel, D A; Tye-Din, J A; Barnardo, M; Salio, M; Jewell, D P; Hill, A V S
Abstract : Background: Current understanding of T cell epitopes in coeliac disease (CD) largely derives from intestinal T cell clones in vitro. T cell clones allow identification of gluten peptides that stimulate T cells but do not quantify their contribution to the overall gluten specific T cell response in individuals with CD when exposed to gluten in vivo. Aims: To determine the contribution of a putative dominant T cell epitope to the overall gliadin T cell response in HLA-DQ2 CD in vivo. Patients: HLA-DQ2+ individuals with CD and healthy controls. Methods: Subjects consumed 20 g of gluten daily for three days. Interferon γ (IFN-γ) ELISPOT was performed using peripheral blood mononuclear cells (PBMC) to enumerate and characterise peptide and gliadin specific T cells before and after gluten challenge. Results: In 50/59 CD subjects, irrespective of homo- or heterozygosity for HLA-DQ2, IFN-γ ELISPOT responses for an optimal concentration of A-gliadin 57–73 Q-E65 were between 10 and 1500 per million PBMC, equivalent to a median 51% of the response for a "near optimal" concentration of deamidated gliadin. Whole deamidated gliadin and gliadin epitope specific T cells induced in peripheral blood expressed an intestinal homing integrin (α4β7) and were HLA-DQ2 restricted. Peripheral blood T cells specific for A-gliadin 57–73 Q-E65 are rare in untreated CD but can be predictably induced two weeks after gluten exclusion. Conclusion: In vivo gluten challenge is a simple safe method that allows relevant T cells to be analysed and quantified in peripheral blood by ELISPOT, and should permit comprehensive high throughput mapping of gluten T cell epitopes in large numbers of individuals with CD.